Pemaknaan Jilbab dalam Pembentukan Perilaku Berbusana Siswi Sekolah SMA Negeri 1 Padangsidimpuan - Nasution, Muktar Hilmi (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
This study stems from the implementation of Regional Regulation of Padangsidimpuan City Number 6 of 2006, which mandates that female students, educators, and educational staff of the Islamic faith wear Muslim attire. After school hours, the use of the hijab varies—some students consistently wear it, others wear it occasionally, and some do not wear it at all. Using a phenomenological approach with a descriptive qualitative method, this study collected data through observation, interviews, and documentation. The findings indicate that female students at SMA Negeri 1 Padangsidimpuan interpret the hijab in three main aspects: social identity, social control, and fashion. This regulation also plays a role in introducing Muslim attire from an early age, shaping dress habits in accordance with religious teachings, and protecting students from foreign fashion influences that contradict religious, cultural, and ethical norms. The factors influencing students' dress behavior include religious understanding, habitual compliance with the regulation, family influence, peer environment, and social media.